DEVELOPING UMKM THROUGH DIGITAL MARKETING IN NTOBO VILLAGE - Dewantara, Fajar; Ilantika, Lusi; Ningsih, Afriza Ade; Febriarta, Elsa Putri; Dwi Pramana, I Kadek Bayu; Prajaka, Wahyu; Rahmi, Maulidatun Nur; Irna, Irna; Henida, Astrid Tsabita; Kurniadi, Adi; Amelia, Novia; Anshari, Buan (Universitas Mataram, 2025)
Ntobo Village, located in Raba District, Bima City, is an interesting area with diverse economic conditions. One of the main aspects of the area's economy is the creative weaving industry which is the backbone for many families in the area and various types of MSMEs, such as culinary crafts, and trade that are developing in this area. However, in marketing, Ntobo Village still relies on traditional methods. This causes the reach of MSME marketing to be limited and less effective in reaching a wider market. Therefore, the Ntobo Village KKN group tries to provide solutions to the problems that occur in the village. The solution we offer is the development and counseling of MSMEs through Digital Marketing through content marketing activities, workshops, education and seminars and participating in other activities, namely improving human resources and other activities.